Corruption and reform in China: an analysis of unintended consequences - Gong, Ting (Crime, law and social change, 1993)
Although market-driven reforms are bringing hope for China's economic development, there has been an increasing visibility of corruption in the reform process. This article examines the relationship between corruption and reform in China by relating the corruption issue to certain reform policies. It finds that corruption results from unintended consequences of some intended reform policies, as these policies aimed at transforming China's socioeconomic structures at the same time inadvertently produce some political and economic conditions conducive to corruption. The unintended consequences are controllable, however, if a balanced reform agenda is developed.